Energy Ministers of the hemisphere promote integration and sustainable development (2001)
Presents the Declaration of Mexco which includes a message to the Heads of State and Government who met in Quebec, Canada on April 20-22, 2001 for the Third Summit of the Americas.
Keywords: ENERGY